Evaluación de la participación de las mujeres desde la perspectiva de Género en las Actividades Agropecuarias de las familias rurales en la cuenca alta del Río Cumbaza-San Martin - Zevallos Rojas, Mary Luz (1999)
The present investigative work constitutes the Thesis " EVALUATION OF THE PARTICIPATION OF WOMEN PROM THE PERSPECTIVE OF GENDER IN AORICULTURE AND ANIMAL HUSBANDRY ACTIVITIES OF THE RURAL FAMILIES IN THE UPPER CUMBAZA RIVER BASIN ". It has as the general objective; evaluate the principal activity of the rural woman in agriculture and animal husbandry activities, determine the areas of decision making about access and control of resources and benefits due to their de monstrative character localized in the communities of Aviación, Chiricyacu, San Roque de Cumbaza and San Antonio de Cumbaza in the Provinces of San Martin and Lamas of the Region San Martín. Within the stages of the participative investigation we weigh the aspects of gender that orient us in analyzing the hypothesis concerning the behavior of the family with the participation of man and woman, specially in concepts of equality, self-esteem, level of decisions, inserted in the peasant economy of the rural society that allows the establishment of roles from the perspective of gender within the communities. The participation of the man and the woman in the different activities or rolls is greatl varied accordins to the location of the communities and based on cultural patterns, one can say that when the community is more distant with the disadvantage for the population maintaine greater dexterity bau with thr comple. Limited ace, limited access to tha economic resoucers and limited participation in communal